2016
DOI: 10.1186/s12879-016-1563-6
|View full text |Cite
|
Sign up to set email alerts
|

Not just a matter of size: a hospital-level risk factor analysis of MRSA bacteraemia in Scotland

Abstract: BackgroundWorldwide, there is a wealth of literature examining patient-level risk factors for methicillin-resistant Staphylococcus aureus (MRSA) bacteraemia. At the hospital-level it is generally accepted that MRSA bacteraemia is more common in larger hospitals. In Scotland, size does not fully explain all the observed variation among hospitals. The aim of this study was to identify risk factors for the presence and rate of MRSA bacteraemia cases in Scottish mainland hospitals. Specific hypotheses regarding ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Alternatively, the difference could reflect other unmeasured confounders including VRE colonization pressure. 39 In our study, 40% of patients with VRE bacteremia died within 30 days of diagnosis. This is similar to the 52% 30-day mortality seen in a large multicenter study in the United States 18 and the 46% 28day mortality in a 10-year single-center study in Korea.…”
Section: Fig 1 Flow Diagrammentioning
confidence: 52%
“…Alternatively, the difference could reflect other unmeasured confounders including VRE colonization pressure. 39 In our study, 40% of patients with VRE bacteremia died within 30 days of diagnosis. This is similar to the 52% 30-day mortality seen in a large multicenter study in the United States 18 and the 46% 28day mortality in a 10-year single-center study in Korea.…”
Section: Fig 1 Flow Diagrammentioning
confidence: 52%
“…[ 30 ] Highly connected hospitals may harbor more MRSA and MRSA bacteremia cases and may have the most potential to transmit HAIs in the entire network. [ 12 , 13 , 31 , 32 ] HAIs may spread at a higher rate than expected at random due to the centralization of patient movement and due to the small average number of transfers required for patients to move throughout the network. A 2012 point prevalence study has shown that HAIs are most prevalent in cancers centers, university hospitals, and armed forces.…”
Section: Discussionmentioning
confidence: 99%
“…Other hospital level risk factors for patient HAI acquisition include larger hospital size and higher patient density and clustering [43][44][45][46][47][48]. Hospitals that are highly connected to one another through a shared health-care system or through a referral system have more patient MRSA bacteremia incidence rates (partial correlation coefficient r = 0.33 (0.28 to 0.38)) [49,50]. Another key hospital design consideration is hospital-acquired pathogen strains may enter into the community through improperly treated hospital wastewater effluent, including MRSA and VRE [51], although discussion of this topic is beyond the scope of this paper.…”
Section: The Hospital Environmentmentioning
confidence: 99%